2005
DOI: 10.1091/mbc.e05-01-0055
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin-dependent Myogenic Cell Differentiation Is Mediated by Both Ca2+/Calmodulin-dependent Kinase and Calcineurin Pathways

Abstract: Arg8-vasopressin (AVP) promotes the differentiation of myogenic cell lines and mouse primary satellite cells by mechanisms involving the transcriptional activation of myogenic bHLH regulatory factors and myocyte enhancer factor 2 (MEF2). We here report that AVP treatment of L6 cells results in the activation of calcineurin-dependent differentiation, increased expression of MEF2 and GATA2, and nuclear translocation of the calcineurin target NFATc1. Interaction of these three factors occurs at MEF2 sites of musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 53 publications
1
40
0
Order By: Relevance
“…Calcineurin appears to act as a co-regulator of muscle hypertrophy with insulin-like growth factor and may also contribute to myogenic proliferation and differentiation of satellite cells during skeletal muscle regeneration (Dunn et al 1999;Musaro et al 1999;Dunn et al 2000;Sakuma et al 2003;Scicchitano et al 2005). The use of calcium / calmodulin inhibitors has been shown to suppress growth of overloaded muscle fibres while calcineurin over expression reduces disuse atrophy (Dunn et al 1999;Dunn et al 2000).…”
Section: Cytoplasmmentioning
confidence: 99%
“…Calcineurin appears to act as a co-regulator of muscle hypertrophy with insulin-like growth factor and may also contribute to myogenic proliferation and differentiation of satellite cells during skeletal muscle regeneration (Dunn et al 1999;Musaro et al 1999;Dunn et al 2000;Sakuma et al 2003;Scicchitano et al 2005). The use of calcium / calmodulin inhibitors has been shown to suppress growth of overloaded muscle fibres while calcineurin over expression reduces disuse atrophy (Dunn et al 1999;Dunn et al 2000).…”
Section: Cytoplasmmentioning
confidence: 99%
“…The gene expressions of myogenin, myosin heavy chain (MHC) and PCNA were assayed by semi quantitative RT-PCR. The primers specific for mouse myogenin and MHC (Table 1) were prepared as described previously (Scicchitano et al, 2005). The primers for PCNA and AR were designed by Primer Express 3.0 software and confirmed to amplify a single product of the expected size via dissociation analysis and gel electrophoresis.…”
Section: Real-time Pcr (Rt-pcr) and Common Pcrmentioning
confidence: 99%
“…Scicchitano et al (32) have recently shown a strong association between acetylation of histone H4 at MEF2 binding sites on genes and increased transcriptional activity of these genes. When L6 myoblasts were treated with arginine vasopressin to induce differenciation, there was a progressive increase in acetylated histone H4 at MEF2 binding sites on myogenin and muscle creatine kinase (MCK) genes that correlated well with the kinetics of the induction of myogenin and MCK mRNA transcripts.…”
mentioning
confidence: 99%